2020
DOI: 10.1001/jamanetworkopen.2019.18504
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ambient and Household Air Pollution With Bone Mineral Content Among Adults in Peri-urban South India

Abstract: IMPORTANCE Air pollution is a major threat to global health. Osteoporosis is responsible for a substantial burden of disease globally and is expected to increase in prevalence because of population aging. Few studies have investigated the association between air pollution and bone health, and their findings were inconclusive. OBJECTIVE To quantify the association between ambient and household air pollution and bone mass in a sample of the general population in peri-urban India. DESIGN, SETTING, AND PARTICIPANT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 56 publications
5
29
0
Order By: Relevance
“…However, some studies have validity, 81 , 82 , 86 , 87 , 94 confounding factor 83 , 91 and subjects follow-up issues. 93 , 94 Four studies were conducted in North and South America (the United States, 85 , 93 Chile 91 and Mexico 94 ); 4 studies were conducted in Europe (Norway, 81 , 82 Romania 83 and Spain 90 ), and the remaining 6 studies were conducted in Asia (Taiwan, 84 , 86 Henan province of China, 87 India 88 and South Korea 89 , 92 ). The total number of participants was 1,024,864, wherein 68,861 were from cross-sectional studies and 956,003 were from cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, some studies have validity, 81 , 82 , 86 , 87 , 94 confounding factor 83 , 91 and subjects follow-up issues. 93 , 94 Four studies were conducted in North and South America (the United States, 85 , 93 Chile 91 and Mexico 94 ); 4 studies were conducted in Europe (Norway, 81 , 82 Romania 83 and Spain 90 ), and the remaining 6 studies were conducted in Asia (Taiwan, 84 , 86 Henan province of China, 87 India 88 and South Korea 89 , 92 ). The total number of participants was 1,024,864, wherein 68,861 were from cross-sectional studies and 956,003 were from cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Two cohort studies had a sample size >100,000 participants, 92 , 93 whereas 8 studies had a sample size of 1000–100,000 participants, 82 , 85–91 and the remaining 5 studies enrolled <1000 patients. 81 , 83 , 84 , 93 , 94 The participants were mainly elderly, 81–84 , 89–91 , 93 followed by middle-aged adults, 86 , 87 , 89 , 92 , 93 young adults 85 , 88 , 93 and pregnant women. 94 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidences evaluating the association between AAP and bone health related biochemical factors is limited [ 4 ]. Some previous studies have concluded associations between air pollution and bone mineral density loss and increased risk of osteoporotic fracture [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%